KELAYAKAN MASKER TRADISIONAL DAUN KELOR UNTUK PERAWATAN KULIT WAJAH KERING - Firsty Madikizella; Murni Astuti (Jurnal Tata Rias dan Kecantikan, 2022)
Traditional moringa leaf masks can be used as an alternative as a natural facial treatment cosmetic for scaly, rough and dull skin. This study aims to: 1) analyze the feasibility of traditional moringa leaf masks judging by the content of vitamins (labor test), 2) analyze the feasibility of traditional moringa leaf masks judging by texture, aroma, and ness (organoleptic test), 3) analyze the feasibility of traditional moringa leaf masks judging by the panelists' fondness (hedonic test). The type of research used is quantitative descriptive research. The variables in this study are free variables (x) and bound variables (Y). Data retrieval techniques using documentation, observations and tests. Data analysis techniques using presentase formulas. Based on the results of laboratory tests shows that the content of Vitamins B1 and C is still present in the traditional mask of moringa leaves. Based on organoleptic and hedonic testing of the traditional feasibility mask of moringa leaves, judging by the texture, most panelists say that the texture of the moringa leaf mask is smooth, for aroma, most panelists say that the moringa leaf mask is strong, for ness, all panelists say that the moringa leaf mask is attached, and for the fondness of panelists most say like a moringa leaf mask.